The Role of Law in the Social and Political Life of the Ukrainian Cossack State (Second Half of the 17th–18th centuries) - STENGACH , Nadiia (University Scientific Notes, 2019)
Among the regulatory and communicative mechanisms of power establishment in the Ukrainian Cossack state is the leading propensity for legal solution of social and political issues — both in the environment of the elite and between the elite and subordinate strata.In the context of court proceedings, it is necessary to highlight the tendency to ensure adversarial process between the plaintiff and the defendant, to create the respondent’s conditions for defense, to direct the court’s work not only to punish, but also to restore justice, to judge impartially and collectively. All this meant rejection of Russian legal norms, which legitimized the «right of the strong».The focus on the impassive legal process was extrapolated to manifestations of both domestic and foreign policy. First of all, this was reflected in the rejection of political actions based on military pressure and coercion, which were recognized as illegitimate ones.In the domestic political aspect, there was the emphasized trend towards constitutional methods of regulating public life. In particular, state institutions purposefully created legal norms in those spheres of public activity where tradition was no longer able to regulate them.In the political and cultural life of the Cossacks’ elite, we also see a clearly defined tendency to regulate legally relations between the participants of the political process. The views formed within such limits denied arbitrariness as a method of solving social and legal problems. However, it should be noted that within the framework of judicial and legal practice of the time, such notions were practically not implemented.The institutional mechanisms of state decision making evolved from the General Council to the Council of General Officer Staff, and then to the representative institution of Ukrainian society — the Sejm. In the evolution of mechanisms for administrative positions, there is a clear tendency to oust the election process and replace it with kinship and clientela relations within the Cossacks’ elite. Nevertheless, the electorate tendencies in the Cossack class remained at the lowest levels of the administrative hierarchy until the decay of the Ukrainian Cossack state. This was due to the fact that the political elite of Hetmanshchyna resisted Russian attempts to interfere with the filling of state posts in Left Bank Ukraine, as well as due to the confrontation of officer groups for dominance over local governments. With the acceptance of ideas of the nobles’ republic by the General Officer Staff, we observe a new strengthening of the electorate institution.Asserting power among representatives of their own social class, the Cossacks’ elite tended to maintain a balance between encouragement and punishment. As for the subordinate classes, the propensity to use punishment and coercion was much more pronounced. There was, however, a marked tendency towards the legislative regulation of the force use. At the political and cultural level, arbitrariness had never been recognized as the lawful actions. Besides, it was not necessary for the Cossacks’ elite to resort to violence to persuade; the pressure of public opinion often was enough.
Keywords: Ukrainian Cossack State; General Council; General Officer Staff; Cossacks’ elite; Cossacks’ law; electivity; democracy; adversarial process